Exploring the therapeutic potential of Sirt6-enriched adipose stem cell-derived exosomes in myocardial ischemia–reperfusion injury: unfolding new epigenetic frontiers - Kun Liu; Hecheng Wang; Yiou Wang; Xiaoxu Zhang; Ruihu Wang; Zhaoxuan Zhang; Jian Wang; Xinran Lu; Xiaoyu Wu; Yanshuo Han (Clinical Epigenetics, 2024)
Abstract Background The management of myocardial ischemia–reperfusion injury (MIRI) presents continuous therapeutic challenges. NAD-dependent deacetylase Sirtuin 6 (Sirt6) plays distinct roles in various disease contexts and is hence investigated for potential therapeutic applications for MIRI. This study aimed to examine the impact of Sirt6-overexpressing exosomes derived from adipose stem cells (S-ASC-Exo) on MIRI, focusing on their influence on AIM2-pyroptosis and mitophagy processes. The sirtuin family of proteins, particularly Sirtuin 6 (Sirt6), play a pivotal role in these processes. This study aimed to explore the potential therapeutic effects of Sirt6-enriched exosomes derived from adipose stem cells (S-ASC-Exo) on regulating MIRI. Results Bioinformatic analysis revealed a significant downregulation of Sirt6 in MIRI subjected to control group, causing a consequential increase in mitophagy and pyroptosis regulator expressions. Therefore, our study revealed that Sirt6-enriched exosomes influenced the progression of MIRI through the regulation of target proteins AIM2 and GSDMD, associated with pyroptosis, and p62 and Beclin-1, related to mitophagy. The introduction of S-ASC-Exo inhibited AIM2-pyroptosis while enhancing mitophagy. Consequently, this led to a significant reduction of GSDMD cleavage and pyroptosis in endothelial cells, catalyzing a deceleration in the progression of atherosclerosis. Extensive in vivo and in vitro assays were performed to validate the expressions of these specific genes and proteins, which affirmed the dynamic modulation by Sirt6-enriched exosomes. Furthermore, treatment with S-ASC-Exo drastically ameliorated cardiac functions and limited infarct size, underlining their cardioprotective attributes. Conclusions Our study underscores the potential therapeutic role of Sirt6-enriched exosomes in managing MIRI. We demonstrated their profound cardioprotective effect, evident in the enhanced cardiac function and attenuated tissue damage, through the strategic modulation of AIM2-pyroptosis and mitophagy. Given the intricate interplay between Sirt6 and the aforementioned processes, a comprehensive understanding of these pathways is essential to fully exploit the therapeutic potential of Sirt6. Altogether, our findings indicate the promise of Sirt6-enriched exosomes as a novel therapeutic strategy in treating ischemia–reperfusion injuries and cardiovascular diseases at large. Future research needs to underscore optimizing the balance of mitophagy during myocardial ischemia to avoid potential loss of normal myocytes.